Prove problem help

  • Thread starter razored
  • Start date
  • #1
razored
173
0
This not homework(self-study book). I do not know where to begin to prove this. This is from "Essentials Calculus" page 45, problem # 11

[tex]f(x) = \left\{ \begin{array}{rcl}{-1} & \mbox{if}& -\infty < x < -1, \\ x & \mbox{if} & -1\leq x\leq1, \\1 & \mbox{if} & 1 < x <\infty ,\end{array}\right[/tex]
[tex]g(x) = \frac {1} {2} |x+1 | - \frac {1}{2}|x-1|[/tex]
Prove that [tex]f(x)\equiv g(x)[/tex]

Latex is awesome :biggrin: First time using it here!
 

Answers and Replies

  • #2
rock.freak667
Homework Helper
6,223
31
where's your attempt at the proof?

But consider what g(x) is for the conditions for f(x)
 
  • #3
Dick
Science Advisor
Homework Helper
26,263
621
Glad you like latex. But, yes, as rock.freak667 points out, split into the three cases that define f.
 
  • #4
razored
173
0
where's your attempt at the proof?

But consider what g(x) is for the conditions for f(x)

Glad you like latex. But, yes, as rock.freak667 points out, split into the three cases that define f.

I don't understand ... "split into the three cases that define f." the cases are listed.

I have no idea where to begin to prove this; a profound explanation would be helpful.
 
  • #5
nicksauce
Science Advisor
Homework Helper
1,272
5
He means split g(x) into the three cases that define f(x). You must show that when x < -1, g(x) = -1, when -1 < x < 1, g(x) = x, and when x > 1, g(x) = 1.
 
  • #6
D H
Staff Emeritus
Science Advisor
Insights Author
15,450
688
Consider this simpler problem:

[tex]f(x) = \begin{cases}-x & \text{if}\ x < 0 \\ \phantom{-}x & \text{if}\ x>=0 \end{cases}[/tex]

[tex]g(x) = |x|[/tex]

For [itex]x>=0[/itex], [itex]g(x)=|x|=x[/tex]. For [itex]x<0[/itex], [itex]g(x)=|x|=-x[/tex]. In both cases, [itex]g(x)=f(x)[/itex]. The functions are identical for all x.

You can do the same thing with your [itex]f(x)[/itex] and [itex]g(x)[/itex]. In particular, what does [itex]g(x)[/itex] evaluate to in each of the three regions?
 
  • #7
mistermath
52
0
If you want to see how to write it formally out you would do something like:
Case 1: Suppose x < -1 then g(x) = ... = f(x)
Case 2: Suppose x > 1 then g(x) = ... = f(x)
Case 3: Suppose -1<=x<=1 then g(x) = ... = f(x)

Two functions f,g are equal in an interval I if f(x)=g(x) for every x in I. (In your case your interval is all real #'s.)
 
  • #8
razored
173
0
Ok. Figured it out, thanks!
 

Suggested for: Prove problem help

  • Last Post
Replies
5
Views
576
Replies
5
Views
423
Replies
52
Views
1K
Replies
9
Views
352
Replies
14
Views
492
Replies
3
Views
456
  • Last Post
Replies
13
Views
608
  • Last Post
Replies
2
Views
259
  • Last Post
Replies
16
Views
1K
Replies
17
Views
497
Top